DEK deficiency suppresses mitophagy to protect against house dust mite-induced asthma - Bai, Qiaoyun; Liu, Ruobai; Quan, Changlin; Han, Xue; Wang, Dandan; Wang, Chongyang; Wang, Zhiguang; Li, Li; Li, Liangchang; Piao, Hongmei; Song, Yilan; Yan, Guanghai (Frontiers in Immunology, 2024)
DEK protein is highly expressed in asthma. However, the mechanism of DEK on mitophagy in asthma has not been fully understood. This study aims to investigate the role and mechanism of DEK in asthmatic airway inflammation and in regulating PINK1-Parkin-mediated mitophagy, NLRP3 inflammasome activation, and apoptosis. PINK1-Parkin mitophagy, NLRP3 inflammasome, and apoptosis were examined after gene silencing or treatment with specific inhibitors (MitoTEMPO, MCC950, and Ac-DEVD-CHO) in house dust mite (HDM) or recombinant DEK (rmDEK)-induced WT and DEK-/- asthmatic mice and BEAS-2B cells. The regulatory role of DEK on ATAD3A was detected using ChIP-sequence and co-immunoprecipitation. rmDEK promoted eosinophil recruitment, and co-localization of TOM20 and LC3B, MFN1 and mitochondria, LC3B and VDAC, and ROS generation, reduced protein level of MnSOD in HDM induced-asthmatic mice. Moreover, rmDEK also increased DRP1 expression, PINK1-Parkin-mediated mitophagy, NLRP3 inflammasome activation, and apoptosis. These effects were partially reversed in DEK-/- mice. In BEAS-2B cells, siDEK diminished the Parkin, LC3B, and DRP1 translocation to mitochondria, mtROS, TOM20, and mtDNA. ChIP-sequence analysis showed that DEK was enriched on the ATAD3A promoter and could positively regulate ATAD3A expression. Additionally, ATAD3A was highly expressed in HDM-induced asthma models and interacted with DRP1, and siATAD3A could down-regulate DRP1 and mtDNA-mediated mitochondrial oxidative damage. Conclusively, DEK deficiency alleviates airway inflammation in asthma by down-regulating PINK1-Parkin mitophagy, NLRP3 inflammasome activation, and apoptosis. The mechanism may be through the DEK/ATAD3A/DRP1 signaling axis. Our findings may provide new potential therapeutic targets for asthma treatment.